Genomic diversity revealed by whole-genome sequencing in three Danish commercial pig breeds. (20th July 2020) - Cai, Zexi; Sarup, Pernille; Ostersen, Tage; Nielsen, Bjarne; Fredholm, Merete; Karlskov-Mortensen, Peter; Sørensen, Peter; Jensen, Just; Guldbrandtsen, Bernt; Lund, Mogens Sandø; Christensen, Ole Fredslund; Sahana, Goutam
Abstract: Whole-genome sequencing of 217 animals from three Danish commercial pig breeds (Duroc, Landrace [LL ], and Yorkshire [YY ]) was performed. Twenty-six million single-nucleotide polymorphisms (SNPs ) and 8 million insertions or deletions (indels) were uncovered. Among the SNPs, 493, 099 variants were located in coding sequences, and 29, 430 were predicted to have a high functional impact such as gain or loss of stop codon. Using the whole-genome sequence dataset as the reference, the imputation accuracy for pigs genotyped with high-density SNP chips was examined. The overall average imputation accuracy for all biallelic variants (SNP and indel) was 0.69, while it was 0.83 for variants with minor allele frequency > 0.1. This study provides whole-genome reference data to impute SNP chip-genotyped animals for further studies to fine map quantitative trait loci as well as improving the prediction accuracy in genomic selection. Signatures of selection were identified both through analyses of fixation and differentiation to reveal selective sweeps that may have had prominent roles during breed development or subsequent divergent selection. However, the fixation indices did not indicate a strong divergence among these three breeds. In LL and YY, the integrated haplotype score identified genomic regions under recent selection. These regions contained genes for olfactory receptors and oxidoreductases. Olfactory receptor genes that might have played a major role in the domestication were previously reported to have been under selection in several species including cattle and swine.